ANALISIS PENGARUH INVESTASI, EKSPOR, INFLASI TERHADAP PERTUMBUHAN EKONOMI DAN KESEJAHTERAAN MASYARAKAT DI PROVINSI BALI - Jayanthi, Ni Kadek Eka (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 8 No 9 (2019): Vol. 8, No.9, September 2019, pp (1947-2194), 2019)
Economic growth is interrelated with the welfare of the public if economic growth is good then the level of income of the public will also increase, besides that from the increase in income that occurs the community will be able to fulfill their needs This study aims to analyze the effect of investment, exports and inflation on economic growth and public welfare in the Province of Bali. This study uses secondary data then analyzed using path analysis data techniques. The results of the research analysis concluded that the investment variable directly had a positive and not significant effect on economic growth in Bali Province. Direct export variables have a positive and significant effect on economic growth in Bali Province, while the inflation variable directly has a negative and significant effect on economic growth in Bali Province. Indirect investment and export variables have no effect on people's welfare, while inflation and economic growth indirectly affect the welfare of the people in Bali Province. Economic growth as an intervening variable of the variables of investment, exports and inflation on the welfare of the people in Bali Province. Keywords : investment, exports, inflation, economic growth, public welfare